Acceptance of virtual reality to promote attention orientation in children: a qualitative study among children with ADHD and neurotypical development - Giuseppina Bernardelli; Sara Arlati; Arianna Scaglione; Elena Saligari; Pamela Frigerio; Aurora Sotgiu; Valeria Flori; Daniela Lucini; Aglaia Vignoli; Andrea Zangiacomi (Annals of Medicine)
Background Immersive Virtual Reality (VR) could be a practical tool for supporting ADHD children in learning to manage their symptoms better. However, VR applications are often addressed to the adolescent/adult population only and few studies have applied VR in children with ADHD.Objective To evaluate the usability and acceptance of a custom-designed VR environment in children with ADHD and with neurotypical development.Methods Nine children aged between 7-11 with ADHD and ten age-matched children with typical development were enrolled and tried the VR environment once. Questionnaires were administered to evaluate technology acceptance and children’s satisfaction. Objective data recorded by the VR application and observations from the therapists while supervising children’s interactions within the virtual scenario were also taken into account.Results No significant differences emerged among the two groups for any of the investigated variables. Satisfaction with the experience was high in both groups. Children specified that they found the VR application very fun, well-organized, and suitable for use. There was a tendency toward a greater appreciation for the usefulness of the VR application among ADHD children compared with their neurotypical peers.Conclusions Results suggest that, beyond individual characteristics and ADHD presence, children generally exhibited a positive attitude toward VR technology; the potential for retaining high levels of involvement, which can positively influence motivation and treatment compliance, was highlighted, thus making the proposed VR environment suitable for future clinical use.